Analytical methods for soluble microbial products (SMP) and extracellular polymers (ECP) in wastewater treatment systems : a review - Kunacheva, Chinagarn (2014)
Effluents from biological processes contain a wide range of complex organic compounds, including soluble microbial products (SMP) and extracellular polymers (ECP), released during bacteria metabolism in mixed culture in bioreactors. It is important to clearly identify the primary components of SMPs and ECPs in order to understand the fundamental mechanisms of biological activity that create these compounds, and how to reduce these compounds in the effluent. In addition, these compounds constitute the main foulants in membrane bioreactors which are being used more widely around the world. A review on the extraction of ECP, characterization, and identification of SMPs and ECPs is presented, and we summarize up-to-date pretreatments and analytical methods for SMPs. Most researchers have focused more on the overall properties of SMPs and ECPs such as their concentrations, molecular weight distribution, aromaticity, hydrophobic and hydrophilic properties, biodegradability, and toxicity characteristics. Many studies on the identification of effluent SMPs show that most of these compounds were not present in the influent, such as humic acids, polysaccharides, proteins, nucleic acids, organic acids, amino acids, exocellular enzymes, structural components of cells and products of energy metabolism. A few groups of researchers have been working on the identification of compounds in SMPs using advanced analytical techniques such as GC–MS, LC-IT-TOF-MS and MALDI-TOF-MS. However, there is still considerably more work needed to be done analytically to fully understand the chemical characteristics of SMPs and ECPs.